Avaliação do impacto de barreiras para adoção de veículos elétricos na cidade de São Paulo - Silva, Robson Francisco da (2024)
According to the increase in global emissions of polluting gases, particularly from vehicles with combustion engines, the search for alternatives to reduce such emissions has become a constant endeavor. The production and marketing of electric vehicles (EVs) is one of these alternatives and has already become a global reality. However, there are barriers and challenges that must be overcome to facilitate the increase in electric vehicles, which brings us to the following research question: What impact do EV barriers have on the adoption of these vehicles in the city of São Paulo? The objective of this study is to evaluate the impact that existing barriers in the city of São Paulo have on the extension of EV adoption, based on an analysis of international literature and validating the results found through a Survey. To achieve this, a systematic literature review was conducted using data collected from the Scopus and Web of Science databases. With this data, a theoretical model was developed to assist in the implementation of a quantitative research study aimed at understanding and validating the existing barriers in São Paulo. The results of the research indicate that the city faces significant environmental barriers related to battery disposal and the disposal of vehicle parts, as well as economic barriers related to maintenance costs, vehicle insurance, the price of replacement parts, and the incentives offered for acquisition. This study provides a significant contribution to the automotive sector by analyzing the existing barriers in São Paulo, as well as offering relevant guidelines for the government regarding environmental issues. Furthermore, the research highlights opportunities for future investigations, aiming to gain a deeper understanding of how to eliminate these barriers and identify new challenges that may emerge in the future.